DNA and RNA Vaccines: Current Status, Quality Requirements and Specific Aspects of Preclinical Studies - A. A. Goryaev; M. V. Savkina; Yu. I. Obukhov; V. A. Merkulov; Yu. V. Olefir (Биопрепараты: Профилактика, диагностика, лечение, 2019)
This review focuses on DNA and RNA vaccines whose potential use was first considered at the end of the 20th century. However, not a single bacterial plasmid-based or mRNA vaccine has been used since that time in public healthcare for the prevention of infectious diseases. Nevertheless, vaccines containing recombinant nucleic acids as the active ingredient still attract interest due to the possibility of rapid development, low-cost production, safety of the technology and the potential to activate cellular and humoral immunity. Recent technological advances have largely overcome the problems of low immunogenicity, instability, and difficulties with the delivery of DNA and RNA vaccines in humans. The aim of this review was to present the main strategies of development of DNA and RNA vaccines designed to prevent infectious diseases, and to summarise requirements for the quality control and preclinical studies. The article examines the general principles of creation of plasmid vectors encoding protective antigens. It describes new technologies used in the creation of DNA vaccines with plasmids encoding an attenuated virus genome (iDNA and PPLAV), and RNA vaccines based on mRNA and self-amplifying RNAs. The article presents current regulatory requirements for the choice of quality parameters to be tested and the general principles of preclinical studies of DNA and RNA vaccines.